Whole-genome sequencing illuminates multifaceted targets of selection to humic substances in Eurasian perch - Ozerov M; Noreikiene Kristina; Kahar Siim; Huss Magnus; Huusko Ari; Kõiv Toomas; Sepp Margot; López María-Eugenia; Gårdmark Anna; Gross Riho; Vasemägi Anti (WILEY, 2022)
Extreme environments are inhospitable to the majority of species, but some organisms are able to survive in such hostile conditions due to evolutionary adaptations. For example, modern bony fishes have colonized various aquatic environments, including perpetually dark, hypoxic, hypersaline and toxic habitats. Eurasian perch (Perca fluviatilis) is among the few fish species of northern latitudes that is able to live in very acidic humic lakes. Such lakes represent almost "nocturnal" environments; they contain high levels of dissolved organic matter, which in addition to creating a challenging visual environment, also affects a large number of other habitat parameters and biotic interactions. To reveal the genomic targets of humic-associated selection, we performed whole-genome sequencing of perch originating from 16 humic and 16 clear-water lakes in northern Europe. We identified over 800,000 single nucleotide polymorphisms, of which >10,000 were identified as potential candidates under selection (associated with >3000 genes) using multiple outlier approaches. Our findings suggest that adaptation to the humic environment may involve hundreds of regions scattered across the genome. Putative signals of adaptation were detected in genes and gene families with diverse functions, including organism development and ion transportation. The observed excess of variants under selection in regulatory regions highlights the importance of adaptive evolution via regulatory elements, rather than via protein sequence modification. Our study demonstrates the power of whole-genome analysis to illuminate the multifaceted nature of humic adaptation and provides the foundation for further investigation of causal mutations underlying phenotypic traits of ecological and evolutionary importance.